Sequencing and characterisation of complete mitogenome DNA for Rasbora sarawakensis (Cypriniformes: Cyprinidae: Rasbora) with phylogenetic consideration. (December 2020) - Lim, Leonard Whye Kit; Kamar, Cynthia Keranti Anak; Roja, Jill Sela; Chung, Hung Hui; Liao, Yunshi; Lam, Tommy Tsan-Yuk; Chong, Yee Ling
Highlights: Sequencing of entire mitogenome of a Borneo Island endemic Rasbora sarawakensis fish species. Gene analysis and phylogenetic maximum likelihood tree conducted to resolve its relationship across other genus members. This study is significant for population genetics and evolution studies. Abstract: The Blueline Rasbora ( Rasbora sarawakensis ) is a small ray-finned fish categorized under the genus Rasbora in the Cyprinidae family. In this study, the complete mitogenome sequence of R. sarawakensis was sequenced using four primers targeting overlapping regions. The mitogenome is 16, 709 bp in size, accommodating 22 transfer RNA genes, 13 protein-coding genes, two ribosomal RNA genes and a putative control region. Identical gene organisation was detected between this species and other genus counterparts. The heavy strand houses 28 genes while the light strand stores the other nine genes. Most protein-coding genes employ ATG as start codon, excluding COI gene, which utilizes GTG instead. The central conserved sequence blocks (CSB-F, CSB-E and CSB-D), variable sequence blocks (CSB-3, CSB-2 and CSB-1) as well as the terminal associated sequence (TAS) are conserved in the control region. The maximum likelihood phylogenetic tree revealed the divergence of R. sarawakensis from the basal region of the Rasbora clade, where its evolutionary relationships with R. maculatus and R. pauciperforata are poorly resolved as indicated by the low bootstrap values. This work acts as steppingstone towards further molecular evolution and population genetics studies of Rasbora genus in future.